Transboundary harm in international law : lessons from the Trail Smelter arbitration / edited by Rebecca M. Bratspies, Russell A. Miller. - Bratspies, Rebecca M., 1965-; Miller, Russell A., 1969- (Cambridge University Press, 2006)
This book reveals the many harms which flow across the ever-more porous sovereign borders of a globalising world. These harms expose weaknesses in the international legal regime built on sovereignty of nation states. Using the Trail Smelter Arbitration, one of the most cited cases in international environmental law, this book explores the changing nature of state responses to transboundary harm. Taking a critical approach, the book examines the arbitration's influence on international law generally, and international environmental law specifically. In particular, the book explores whether there are lessons from Trail Smelter that are useful for resolving transboundary challenges confronting the international community. The book collects the commentary of a distinguished set of international law scholars who consider the history of the Trail Smelter arbitration, its significance for international environmental law, its broader relationship to international law, and its resonance in fields beyond the environment.